Surface Wrinkling versus Global Buckling Instabilities in Thin Film‐Substrate Systems under Biaxial Loading: Direct 3D Numerical Simulations (Adv. Theory Simul. 9/2022). Issue 9 (11th September 2022) - Nikravesh, Siavash; Ryu, Donghyeon; Shen, Yu‐Lin
Abstract : Surface Wrinkling versus Global Buckling Instabilities in Thin Film‐Substrate Systems In article 2200183, Nikravesh, Ryu and Shen develop a computational strategy to directly simulate complex surface wrinkles and structural buckling of the thin film‐compliant substrate structure, covering the entire biaxial loading spectrum and providing mechanistic rationale for the evolution of local wrinkle configurations mediated by global buckling.